Новые виды клещей семейства Pygmephoridae (Tarsonemina, Trombidiformes) - Севастьянов, В.Д. (Вестник зоологии, 1981)
Six new mite species of the family Pygmephoridae are described: Bakerdania laricophilla sp. n. from Carabus coriaceus (Khmelnitsky Region, Ukr. SSR); Pygmephorellus artemjevisp. n. in soil under wheat(Tatar ASSR); Pediculaster sterculinicola sp. n. in cow manure in forest (KhemInitsky Region, Ukr. SSR); Microdispus acuminatus sp. n. and M. minutus sp. n. on ants Tetramorium caespitum (Odessa environs); Unguidispus contematosus sp. n. in ant-hills of Lasius fuliginosus (Khmelnitsky Region, . SSR). The family Microdispidae Cross, 1965 is interpreted by the author as the tribe Microdispini Cross, 1965.